Iowa Birdline update, August 14, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for August 14, 1989. Highlights include more shorebird sightings, the beginning of the passerine migration and an update on the released Peregrine Falcons. Epson - sheet feed/flatbed